UTILIZATION OF SOLAR ENERGY AS AN ALTERNATIVE ENERGY SOURCE IN THE HYDROGEN (H2) PRODUCTION PROCESS IN HYDROFILL - Romadhon, Bima; Saleh, Choirul; Setiawan, Rachmadi; Megawati, Citra Dewi (Journal of Sustainable Technology and Applied Science (JSTAS), 2022)
ABSTRACT: Due to the industrial revolution, global demand for oil rose as did hydrogen. Given the population explosion, energy demand is rising to a very large level and this results in excessive exploitation of natural resources and greenhouse gas deposits. But since the 2015 Paris Agreement, the attention of international bodies and climate movements has made drastic policy toward the use of renewable energy, with the gradual elimination of fossil fuels. One of the key challenges to reducing greenhouse gas emissions and addressing the growing global energy demand is with environmentally friendly and sustainable energy solutions. Hydrogen is recognized as a potential fuel because it offers a carbon-free solution, a high caloric value compared to fossil fuels. Hydrogen can be produced from a wide variety of domestic resources. Currently, most hydrogen is produced using Steam Methane Reforming (SMR) and Carbon Capture and Storage (CCS) natural gas or coal gasification is the cheapest way in terms of cost compared to using electrochemistry and renewable biomass as the main ingredients of hydrogen production. Electrolysis methods were applied in this study to produce hydrogen fuel. The purpose of this test was to compare the effectivity of electrolysis system production in room temperature conditions (VH2real) and ideal conditions (VH2ideal) with energy consumption (Vcell) per liter of H2. From the tests that have been conducted, it can be concluded that the ideal condition of an electrolysis system is difficult to achieve in room temperature conditions, the results showed in ideal conditions, the expected hydrogen volume of 18.23 liters was obtained with a power consumption of 6,390 Watts / Liter, but in the room conditions the average test results showed that the average power consumption consumed was 6,633 Watts / Liter.